Consequences of financial reporting quality on corporate performance: Evidence at the international level - Jennifer Martínez-Ferrero (Estudios de Economía, 2014)
This paper examines the consequences of Financial Reporting Quality (FRQ) on Corporate Performance, using three proxies of FRQ: (i) earnings quality; (ii) conservatism; and (iii) accruals quality. Our purpose is to analyze the effect of a good FRQ on financial performance (FP) measured by the market to book ratio. To this end, the proposed hypotheses are tested on an unbalanced sample of 1, 960 international non-financial listed companies from 25 countries and the special administrative region of Hong-Kong for the period 2002-2010. The use of simultaneous equations for the panel data, via the GMM estimator proposed by Arellano and Bond (1991), highlights the positive effect of financial reporting quality (FRQ) on financial performance. This result is robust according to the different measurements of FRQ (earnings quality, accruals quality and accounting conservatism) and for an aggregated measure for the previous three proxies of FRQ. The empirical evidence shows that this relationship is moderated by the level of corruption perception in the country of origin of the company, the adoption of IFRS, the accounting system used in the country and the influence of the economic cycle.
Keywords: M41; 330; Financial Reporting Quality (FRQ); Financial Performance (FP); Accruals Quality (AQ); Earnings Quality (EQ); Accounting Conservatism